Prevalence of depression and its correlates among undergraduate health science students in Mogadishu, Somalia: a cross-sectional study - Bashiru Garba; Samiro Ali Mohamed; Maria Mowlid Mohamed; Hodo Aideed Asowe; Najib Isse Dirie; Yushau Umar; Jamal Hassan Mohamoud; Mohamed Hussein Adam; Jihaan Hassan; Fartun Abdullahi Hassan Orey; Abdullahi Abdirahman Omar; Ibrahim Abdullahi Mohamed; et al. (BMC Psychiatry)
Abstract Background Depression among undergraduate health science students is increasingly recognized as a significant public health issue globally. These students face immense academic pressure, often leading to stress and mental exhaustion, particularly for students studying in a humanitarian crisis situation. However, there is a scarcity of information in this regard in higher education institutions in Somalia. Hence, this investigation was conducted to assess the prevalence of depression and its correlates health science students in Somalia. Methods A cross-sectional study was conducted on 321 health science students from some universities in Mogadishu, Somalia. The data was collected from students studying medicine, nursing and midwifery, laboratory science and public health at SIMAD university, Banadir university, Mogadishu university and Jamhuriya university, all located in Mogadishu. Simple random sampling based on class list was used to select the participants and a web-based self-administered Patient Health Questionnaire (PHQ-9) was used to screen for depression. The collected data were cleaned and checked for completeness before exporting into SPSS version 27 Statistical software for analysis, where descriptive statistics as well as logistic regression analysis was done to determine the independent predictors of the outcome variable. Significant association was determined at a 95% confidence interval and p-value < 0.05. Result The prevalence of depression among the students was 58.6%. A total of 41.5% (133/321) of the participants were free from depression (Normal), while 30.8% had mild depression, 27.1% had moderate depression and 0.6% had severe depression. Analysis of the association between the sociodemographic variables and depressive state of the participant showed statistical significance (p-value = 0.045) for course of study. Students studying nursing and midwifery had the highest case of depression with 68.6% (59/86), followed by public health 66.7% (30/45), laboratory science 52.3% (34/65), and medicine having the least number of depressed students with 52.0% students (65/125). Similarly, gender of students was also found to be statistically significant (p-value = 0.001) with female students having 65% depression which is 41.1% of the total students studied. Conclusion The prevalence of depression among health science students in Mogadishu was high and positively associated with gender, having trouble with authorities, emotional problems, as well as experience of sexual abuse or violence. Hence, routine screening and monitoring of students’ mental health state on the campus and providing mental health services is necessary to address this growing problem.